PI4KIII inhibitor enviroxime impedes the replication of the hepatitis C virus by inhibiting PI3 kinases. (14th September 2018) - Delang, Leen; Harak, Christian; Benkheil, Mohammed; Khan, Hayat; Leyssen, Pieter; Andrews, Martin; Lohmann, Volker; Neyts, Johan
Abstract: Objectives: Many positive-stranded RNA viruses, including HCV, drastically remodel intracellular membranes to generate specialized environments for RNA replication. Phosphatidylinositol 4-kinase III (PI4KIII)α plays an essential role in the formation of HCV replication complexes and has therefore been explored as a potential drug target. Here, we characterized the anti-HCV activity of the PI4KIII inhibitors enviroxime and BF738735 and elucidated their mechanism of action. Methods: Antiviral assays were performed using HCV subgenomic replicons and infectious HCV. Enviroxime- and BF738735-resistant HCV replicons were generated by long-term culture with increasing compound concentrations. Intracellular localization of phosphatidylinositol 4-phosphate (PI4P) lipids was analysed by confocal microscopy. Results: HCV subgenomic replicons resistant to either enviroxime or BF738735 proved cross-resistant and carried mutations in the NS3, NS4B and NS5A genes. Knockdown of PI4KIIIβ by small interfering RNA (siRNA) did not affect the replication of the HCV subgenomic replicon in this study. Furthermore, the compounds did not affect PI4P lipid levels at the replication complexes nor the phosphorylation status of NS5A, activities attributed to PI4KIIIα. Interestingly, the broad-spectrum phosphoinositide 3-kinase (PI3K) inhibitor LY294002 proved to be 10-fold less effective against the resistant replicons. In addition, enviroxime and BF738735 inhibited several PI3Ks in enzymatic assays. Conclusions: Contrary to assumptions, our data indicate that PI4KIIIα and PI4KIIIβ are not the main targets for the anti-HCV activity of enviroxime and BF738735. Instead, we demonstrated that both molecules impede HCV replication at least partially by an inhibitory effect on PI3Ks. Moreover, HCV is able to bypass PI3K inhibition by acquiring mutations in its genome.